Ultrasonographic Findings of Successful Polyvinylidene Fluoride Mid‐Urethral Sling Surgery and Their Clinical Relevance - Wen‐Chen Huang; Evelyn Yang; Jenn‐Ming Yang (Neurourology and Urodynamics, 2026)
ABSTRACT Objectives This study investigated the postoperative sonographic characteristics of polyvinylidene fluoride (PVDF) suburethral tape used to treat stress urinary incontinence. Materials and Methods We conducted a retrospective study at a tertiary urogynaecological clinic by reviewing the data of 20 matched pairs of patients who underwent mid‐urethral sling surgery using either polypropylene (PP) or PVDF suburethral tapes. Three months after surgery, we performed pelvic ultrasound, conducted in‐person interviews, and administered a validated questionnaire. Ultrasound was used to evaluate the urethral location of the tape in relation to the entire urethra, any urethral encroachment at rest, and the interaction between the tape and urethra during the Valsalva maneuver. Results At the 3‐month postoperative evaluation, the median urethral position of the tape did not differ significantly between the two groups (PVDF: 63rd percentile; PP: 61st percentile; p = 0.342). Urethral encroachment at rest was observed in 5% (1/20) of patients in the PVDF group, compared to 65% (13/20) in the PP group, which was statistically significant ( p < 0.001). During the Valsalva maneuver, dynamic urethral kinking occurred in 10% (2/20) of the PVDF group and 30% (6/20) of the PP group ( p = 0.125). Furthermore, no significant correlation was identified between the static characteristics of the tape and its dynamic interactions within the PVDF group ( p = 0.335). Conclusions PVDF demonstrates enhanced safety and efficacy, suggesting its potential as a superior material for mid‐urethral sling surgeries. Further research with a larger sample size and long‐term follow‐up is necessary to validate these findings.